(untitled) (Acta Scientiarum. Health Sciences, 2019)
High levels of reactive oxygen species can trigger an imbalance in redox status, which generates oxidative damage in macromolecules. The present study aimed to investigate the influence of oral supplementation with benfotiamine on oxidative stress and antioxidant activity in muscle of trained mice. Twenty-five male Balb/c mice were placed in groups. Sta-Sed: standard diet and sedentary (n = 6); Ben-Sed: benfotiamine supplemented and sedentary (n = 6); Sta-Tr: standard diet and trained (n = 6); and Ben-Tr: benfotiamine supplemented and trained (n = 7). Standard diet was AIN-93 growth and supplemented diet was AIN-93 with benfotiamine (500 mg kg-1). Trained mice were submitted to 6-weeks of endurance swimming training. The concentration of thiobarbituric acid reactive substances (TBARS), non-protein thiols, catalase (CAT) and superoxide dismutase activities (SOD) were analyzed in the gastrocnemius muscle. TBARS concentration was lower in the Ben-Tr group than in Ben-Sed and Sta-Tr groups. Thiol levels were higher in the Ben-Sed group than in the non-supplemented groups. CAT activity was more pronounced in both supplemented groups while SOD activity was higher in the Ben-Tr group than in the non-supplemented groups. The results show that benfotiamine supplementation is effective in enhancing antioxidant defenses and reducing oxidative damage in muscle of endurance-trained mouse.